MECHANICAL COMPOSITION OF IRRIGATED MASSIVE SOILS NAMED AFTER I. DIYORO, SARIASA DISTRICT (Conferencea, 2023)
The article presents information on the distribution of soils, general properties and mechanical composition of irrigated tyupical gray, meadow-gray, and swamp-meadow soils of the Sariosi region of the Surkhon Darya region. The mechanical composition of these soils is closely related to such factors as the composition of irrigation water, the pover of agricultural irrigation,the duration of the irrigation period, and even the formation of soils of different mechanical composition in different areas of the territory. A field irrigated from a single ditch. Also, taking into account the mechanical composition, recommendations are given aimed at carrying out agrotechnical and agrophysical measures on these soils.